Fluoroscopic and tomographic correlation for aortic annulus measurements in transcatheter aortic valve implantation: “follow the right cusp” rule - Héctor A. Álvarez-Covarrubias; Markus Kasel; Jonathan M. Michel; Salvatore Cassese; Sebastian Kufner; Charlotte Duesmann; Constanza Pellegrini; Tobias Rheude; N. Patrick Mayr; Heribert Schunkert; Adnan Kastrati; Erion Xhepa; et al. (REC: Interventional Cardiology (English Ed.), 2023)
ABSTRACT Introduction and objectives: Coronary computed tomography angiography (CCTA) has become the gold standard to measure the size of the aortic annulus and better select the size of transcatheter heart valves (THV) in patients undergoing transcatheter aortic valve implantation (TAVI). However, in selected cases, CCTA may not be feasible. Angiographic aortic annulus (AAA) measurements during TAVI may be an alternative and should be evaluated for precision regarding the proper selection of THV sizes. We sought to investigate the correlation between AAA and CCTA measurements for the proper selection of balloon-expandable valve (BEV) sizes in patients undergoing TAVI. Methods: Patients undergoing TAVI with BEV and high-quality CCTA were included. AAA measurements were obtained in the standard 3-cusp view after aortic root aortography. Angiographic distance between non- and left coronary cusps were compared to CCTA annulus measurements. Endpoints were diagnostic tests and correlations between angiographic and CCTA measurements, and the composite endpoint of the VARC-3-defined efficacy (technical success, correct position, and intended performance), and safety profile (multiple valves, valve embolization, pacemaker implantation, and more than moderate valvular regurgitation). Results: Regarding the Sapien family of THV, aortography-based distance measurements showed a correlation of 0.528 (P < .01), 0.451 (P < .01), and 0.579 (P < .01) for 23 mm, 26 mm, and 29 mm valves with CCTA-based distance measurements. No difference was seen regarding the VARC-3-defined efficacy (94.2% vs 96.0%; P = .60) and safety profile (90.9% vs 91.9%; P = .84) among cases showing discordant and concordant pairs of measurements. Conclusions: AAA measurement showed a moderate diagnostic test and Spearman’s correlation coefficient compared to CCTA-based annulus assessment for perioperative THV size selection. This strategy could potentially enable TAVI in patients in whom access to preoperative CCTA is not available.